2012
DOI: 10.1084/jem.20121172
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of a death receptor renders antiviral T cells susceptible to NK cell–mediated deletion

Abstract: Hepatic NK cells eliminate HBV-specific T cells dependent on TRAIL and TRAIL-R2 interactions to limit antiviral immunity in chronic infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
274
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(290 citation statements)
references
References 48 publications
13
274
1
2
Order By: Relevance
“…Many research groups have shown that NK cells in patients with chronic hepatitis B become defective in terms of producing IFN-c with preserved cytotoxic activity [31][32][33][34][35]. Furthermore, TRAIL (TNF-related apoptosis-inducing ligand)-expressing NK cells eliminate HBV-specific T cells which highly express the TRAIL death receptor TRAIL-R2 [36]. Upon antiviral therapy, IFN-c production by NK cells is partially restored through the downregulation of NKG2A [35].…”
Section: Nk Cells and Dcs In Chronic Hbv Infectionmentioning
confidence: 99%
“…Many research groups have shown that NK cells in patients with chronic hepatitis B become defective in terms of producing IFN-c with preserved cytotoxic activity [31][32][33][34][35]. Furthermore, TRAIL (TNF-related apoptosis-inducing ligand)-expressing NK cells eliminate HBV-specific T cells which highly express the TRAIL death receptor TRAIL-R2 [36]. Upon antiviral therapy, IFN-c production by NK cells is partially restored through the downregulation of NKG2A [35].…”
Section: Nk Cells and Dcs In Chronic Hbv Infectionmentioning
confidence: 99%
“…Some recent studies indicated that NK cells have a suppressive role in anti-viral immunity (e.g., during LCMV and HBV infection). 120,121 NK cells were shown to negatively regulate antiviral immunity in chronic HBV infection by eliminating HBV-specific CD8 1 T cells in a contact-dependent manner by inducing apoptosis. 121 Apoptosis induction by NK cells might be one of the reasons HCC-specific CD8 1 T cells are reduced in HBV-related HCC.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…120,121 NK cells were shown to negatively regulate antiviral immunity in chronic HBV infection by eliminating HBV-specific CD8 1 T cells in a contact-dependent manner by inducing apoptosis. 121 Apoptosis induction by NK cells might be one of the reasons HCC-specific CD8 1 T cells are reduced in HBV-related HCC. 122 Further studies are needed to delve into the opposing roles of NK cells in CHB to substantively exploit the potential of NK cells to treat chronic HBV infection and HCC.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…It has been reported that NK cells regulate T cell responses through multiple direct and indirect mechanisms, including NK cell-mediated killing of activated CD8 + T cells (14,15,(18)(19)(20)(21), CD4 + T cells (18,19,22,23), and also of dendritic cells (DCs) (12,24,25). However, little is known about a possible NK cell-mediated inhibitory/regulatory role during antitumor immune responses.…”
mentioning
confidence: 99%